Patient-provider care goal concordance: implications for palliative care decisions. Issue 8 (3rd August 2019) - Ellis, Erin M.; Orehek, Edward; Ferrer, Rebecca A.
Abstract: Objective : Goal-concordant care is an important feature of high quality medical treatment. Patients' care goals may focus on curative and/or palliative outcomes. Patients rarely communicate their care goals, and providers' predictions of patient goals are often inaccurate, corresponding most closely to their own treatment goals. This projection of own goals onto patients introduces the potential for bias, leading to goal-discordant care. Design and Main Outcomes : We examined goal discordance using data from a U.S. sample of healthcare providers ( N  = 492) recruited online in 2017 using GfK Knowledge Panel. Providers reported their perceptions of their patients' care goals (curative relative to palliative), their own care goals if they were to become ill, and their willingness to deliver palliative care. Results : For 28% of providers, their own care goals differed from their patients'. Providers were more likely to prioritise palliative care (relative to curative) in their own goals than in their predictions about patients' goals. Providers were more willing to deliver palliative care when their own goals prioritised more palliative relative to curative care, but their perceptions of patient goals were unassociated with willingness to provide it. Conclusions : Efforts to improve goal communication and reduce projection biases among providers may facilitate goal-concordant care.